Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/art.41012
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy, Tolerability, and Joint Safety of Fasinumab in Osteoarthritis Pain: A Phase IIb/III Double‐Blind, Placebo‐Controlled, Randomized Clinical Trial

Abstract: ObjectiveTo prospectively assess the efficacy, general safety, and joint safety of fasinumab, an anti–nerve growth factor monoclonal antibody, in osteoarthritis (OA) hip and/or knee pain.MethodsPatients with moderate‐to‐severe OA pain (knee or hip) and history of inadequate response or intolerance to analgesics were randomized to receive fasinumab (at 1 mg, 3 mg, 6 mg, or 9 mg) or placebo every 4 weeks over 16 weeks and were followed up to week 36. Efficacy end points were the change from baseline to week 16 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 27 publications
3
60
1
1
Order By: Relevance
“…NGF induces sensitization of peripheral nociceptive terminals as well as the development of the nervous system, and plays a key role in acute and chronic pain [33]. Biologic agents that specifically block NGF revealed dramatic pain relief among OA patients, and despite their unique side effect profile, such as alterations in peripheral sensation and development of arthropathies, they are in active clinical development [34,35] [36]. Surgically induced OA models reflect posttraumatic human OA and include destabilization of the medial meniscus (DMM), anterior cruciate ligament transection (ACLT), and medial meniscal transection (MNX) models.…”
Section: Pain In Clinical Oamentioning
confidence: 99%
“…NGF induces sensitization of peripheral nociceptive terminals as well as the development of the nervous system, and plays a key role in acute and chronic pain [33]. Biologic agents that specifically block NGF revealed dramatic pain relief among OA patients, and despite their unique side effect profile, such as alterations in peripheral sensation and development of arthropathies, they are in active clinical development [34,35] [36]. Surgically induced OA models reflect posttraumatic human OA and include destabilization of the medial meniscus (DMM), anterior cruciate ligament transection (ACLT), and medial meniscal transection (MNX) models.…”
Section: Pain In Clinical Oamentioning
confidence: 99%
“…As a result to a research into various clinical trial registers (Arthritis Clinical Trials, Clinical Research and Drug Information) and on specialized e-platforms, 5 randomized, multicentric double-blind clinical studies (20)(21)(22)(23)(24) have been identified, which monitored the efficiency of various biological molecules in the treatment of arthrosis (etanercept, adalimumab, litikizumab, fasinumab and tanezumab).…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, a category search is unavailable in the TRIP. Evidence may be found either by search terms that match the PICO components (Patient, Intervention, Comparison, [19]; 2) a double blind phase IIb/III RCT of using fasinumab for osteoarthritic pain, reported by Dakin P. et al [20]; 3) «a mixed methods study protocol» as to effectiveness, cost-utility, and benefit of a multicomponent therapy to improve the quality of life of patients with FM in primary care, by Caballol Angelats R. et al [21]; 4) a mixed method evaluation of a primary care-based opioid's acceptability for chronic non-cancer pain, conducted by Kesten J. et al [22]. We are reporting the obtained results, taking into account their novelty.…”
Section: оригінальні дослідження / Original Researchesmentioning
confidence: 99%
“…Dakin P. et al concluded that fasinumab alleviated OA pain and improved function even when analgetics were ineffective. They suggested an expediency of further studying «the lowest doses of fasinumab in patients with knee or hip ОА» [20].…”
Section: оригінальні дослідження / Original Researchesmentioning
confidence: 99%